Opportunities and Challenges in the Work of Natural Science Teachers During Online Teaching: Teachers’ Beliefs and Attitudes - Mirosavljević, Ana; Bognar, Branko; Sablić, Marija (Acta Paedagogica Vilnensia, 2023)
The COVID-19 pandemic has had a catastrophic impact on all sectors of the economy worldwide, including education. This led to the closing of schools, soon followed by online teaching that replaced traditional classroom teaching for the duration of the pandemic. This case study is relevant to examining natural science teachers’ attitudes and beliefs about online teaching and the challenges they faced during the pandemic. Data were collected using standardized, open-ended interviews with six outstanding natural science teachers from elementary schools. In this article, we explore the work-related challenges and opportunities experienced by outstanding teachers because of the COVID-19 pandemic and the introduction of online teaching. The results of the study show that teachers are open to changes and express relatively positive attitudes and beliefs about online teaching during the COVID-19 crisis, such as using a variety of digital tools during online teaching and after returning to classroom teaching. They are developing and improving their digital competences as well as their self-reflection skills, which give them the space they need to reflect consciously and deeply on their teaching. However, they encounter various obstacles to teaching online, such as technical difficulties, difficulties in assessment, excessive parental involvement in children’s work, etc. The efforts to develop personally and professionally improve the quality of pedagogical work, including distance learning, and contribute to the development of teachers’ professional identity. The limitation of this study is relatively small group of teachers who participated in the research, i.e., only six of them.
Keywords: online teaching; COVID-19; natural science teachers